2021
DOI: 10.3390/jcm10051111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture in Pain Management of Head and Neck Cancer Radiotherapy: Prospective Randomized Unicentric Study

Abstract: This prospective randomized open-label trial aimed to evaluate the role of acupuncture in the treatment of pain related to curative and adjuvant (chemo)radiotherapy of head and neck cancer. Patients in two arms (30 patients in each arm) underwent standard oncology therapy and standard supportive care with or without acupuncture. The stratification factors were the type of treatment and chemotherapy indication. The toxicity assessed was represented by pain rated on a 10-point pain scale and analgesic use. Avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Vale ressaltar que a auriculoterapia é uma técnica de baixo custo e segura para os pacientes, gerando menos efeitos adversos, que são bastante recorrentes nos pacientes oncológicos (Dymackova et al, 2021). Como há elevada prevalência de efeitos colaterais e dores da doença não resolvidos nestes indivíduos com câncer, é primordial que se adote um melhor gerenciamento dos sintomas e uma minimização dos eventos adversos, visto que, além de toda a carga que a doença traz, os pacientes também enfrentam os efeitos colaterais dos tratamentos (Contim, Santo e Moretto, 2020).…”
Section: Resultsunclassified
“…Vale ressaltar que a auriculoterapia é uma técnica de baixo custo e segura para os pacientes, gerando menos efeitos adversos, que são bastante recorrentes nos pacientes oncológicos (Dymackova et al, 2021). Como há elevada prevalência de efeitos colaterais e dores da doença não resolvidos nestes indivíduos com câncer, é primordial que se adote um melhor gerenciamento dos sintomas e uma minimização dos eventos adversos, visto que, além de toda a carga que a doença traz, os pacientes também enfrentam os efeitos colaterais dos tratamentos (Contim, Santo e Moretto, 2020).…”
Section: Resultsunclassified
“…All of the studies included in this review indicated that acupuncture had relatively few undesirable side effects (Vinjamury et al 2013, Tas et al 2014, Lam et al 2017, Wei-Min and Li 2021, Dymackova et al 2021, He et al 2022). In addition, as well as its effect on cancer related pain, Vinjamury et al (2013), Tas et al (2014), Wei-Min and Li (2021) and Dymackova et al…”
Section: Side Effectsmentioning
confidence: 96%
“…In the included studies, the analgesic effect of acupuncture was reported to be in association with other pain management interventions, not as a stand-alone therapy. Two studies specifically noted that acupuncture could reduce the amount of analgesic medication required by people living with cancer (Dymackova et al 2021, He et al 2022. None of the reviewed studies suggested that acupuncture increased analgesic use.…”
Section: Level Of Analgesic Usementioning
confidence: 99%
See 1 more Smart Citation
“…138 Recent studies have shown that AC is an effective and reliable treatment for cancer pain, [26][27][28] with fewer adverse effects 29 and the ability to reduce the amount of narcotic analgesics needed. [30][31][32]132,133 One case report suggested that AC significantly improved neuropathic pain caused…”
Section: Acupuncture For Cancer-related Painmentioning
confidence: 99%